Proceedings of the 54th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2016
DOI: 10.18653/v1/p16-1040
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Based Neural Word Segmentation

Abstract: Character-based and word-based methods are two main types of statistical models for Chinese word segmentation, the former exploiting sequence labeling models over characters and the latter typically exploiting a transition-based model, with the advantages that word-level features can be easily utilized. Neural models have been exploited for character-based Chinese word segmentation, giving high accuracies by making use of external character embeddings, yet requiring less feature engineering. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 28 publications
(51 reference statements)
2
103
1
Order By: Relevance
“…But both of them rely heavily on massive handcrafted features. Contemporary to this work, some neural models (Zhang et al, 2016a;Liu et al, 2016) Another notable exception is (Ma and Hinrichs, 2015), which is also an embedding-based model, but models CWS as configuration-action matching. However, again, this method only uses the context information within limited sized windows.…”
Section: Related Workmentioning
confidence: 99%
“…But both of them rely heavily on massive handcrafted features. Contemporary to this work, some neural models (Zhang et al, 2016a;Liu et al, 2016) Another notable exception is (Ma and Hinrichs, 2015), which is also an embedding-based model, but models CWS as configuration-action matching. However, again, this method only uses the context information within limited sized windows.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, deep learning methods have been widely used in many nature language processing tasks, such as name entity recognition (Lample et al, 2016), zero pronoun resolution (Yin et al, 2017) and word segmentation (Zhang et al, 2016). The effectiveness of neural features has also been studied for this framework Watanabe and Sumita, 2015;Andor et al, 2016).…”
Section: Related Workmentioning
confidence: 99%
“…The neural network with its non-linearity is in theory able to learn bigrams by conjoining unigrams, but it has been 4 Our calculation of BTS FLOPs is very conservative and favorable to BTS, as detailed in the supplementary material. shown that explicitly using character bigram features leads to better accuracy (Zhang et al, 2016;Pei et al, 2014). Zhang et al (2016) suggests that embedding manually specified feature conjunctions further improves accuracy ('Zhang et al (2016)-combo' in Table 4).…”
Section: Segmentationmentioning
confidence: 99%